Who makes the financial decisions in Singapore households? - Ang, Yee Wee (2008)
The purpose of this study is to investigate whether the financial decision making styles of our sample are consistent with the postulations of the bargaining model or the unitary model. In addition, this study seeks to determine whether financial decision making in Singapore households are husband-dominated, wife-dominated, or jointly made. Factors that influence the financial decision making style are also analyzed. With the emergence of dual-income households in Singapore, both husband and wife are likely to exert influence when making decisions. Hence, economic models on household decision making which assumes a single decision maker in the household are no longer appropriate in providing a realistic depiction of how decisions are made within Singapore households. Thus, models that incorporate a bargaining process appear to be able to better explain household behaviour in Singapore.